Problems and Challenges of Asymmetrical Democracy in Indonesia - Kusuma, Rizky Dwi; Fauzi, Anwar; Saepudin, Saepudin; Randisa, Azis Reza (Kybernology : Journal of Government Studies, 2023)
This study delves into the challenges and issues arising from asymmetrical democracy in Indonesia, focusing on local political dynamics in regions such as Aceh, Papua, Jakarta, and Yogyakarta (DIY). Through qualitative analysis, researchers assessed how political autonomy and hierarchical administrative structures influence checks and balances within local institutions. In Aceh and Papua, significant issues were identified concerning the perception of political autonomy by regents and mayors, which contrasts with special laws designating the governor as the primary authority. Both regions highlight how historical conflicts and separatist aspirations shape governance structures and local democratic management. Jakarta, with its unique model, demonstrates how the governor's exclusive power at the provincial level can impact inter-governmental interactions and local interests. Meanwhile, in Yogyakarta, the sultan's dominance as governor raises questions about the quality of local democracy and the potential safeguarding of the sultan's interests. These findings underscore the urgent need for stringent checks and balances and clear delineation of authority to ensure effective local governance amidst the challenges of asymmetrical democracy in Indonesia.